An efficient hybrid wave/photovoltaic scheme for energy supply in remote areas. (11th January 2011) - El-Sayed, Mohamed A.H.; Sharaf, Adel M.
This paper presents the efficient utilisation of hybrid photovoltaic/wave energy system for desalination water pumping and supplying the local AC and DC loads. The novel hybrid system comprises eight key parts. The PV array and wave energy permanent magnet linear generator (PMLG) as energy sources, novel AC side modulated power filter compensator (MPFC), AC-DC converter, novel DC side green plug power filter (GPF), DC permanent magnet motor for water pumping station PMDC, DC local load, interfacing DC-AC inverter to the public grid, inverter controller and AC load for supplying the additional electric demand. The proposed hybrid system with all subsystems has been digitally simulated using the Matlab Simulink/Sim-Power software environment. In addition, the novel dynamic error driven control system is also simulated and the performance and dynamic characteristics of the controllers is tested for PMDC motor torque variation, changing variables of renewable sources and load excursions. The dynamic performance of the unified green wave energy utilisation system is assessed using the coordinated dynamic error driven regulators.